Literature Review: Pengaruh Pijat Oksitosin terhadap Involusi Uterus pada Ibu Postpartum: Literature Review: The effect of Oxytocin Massage on Uterine Involution in Postpartum Mothers - Siti Fatimah (Universitas Ngudi waluyo, 2024)
The involution process during postpartum is a crucial physiological mechanism to avoid postpartum complications. One effort to support uterine involution is with oxytocin massage. There has been a lot of research on oxytocin massage but its effectiveness has not been studied in a wider environment. This study aims to examine articles on the effect of oxytocin massage on uterine involution in postpartum mothers. Researchers used three databases, namely Google Scholar, PubMed and Scopus. Full text, free articles published in the 2014-2024 range with keywords. The keywords used are “pijat oksitosin”, “involusi uterus”, “ibu nifas” in Indonesian. The keywords used in English are